1992
DOI: 10.1007/bf00317778
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between year classes in the benthic amphipod Monoporeia affinis: effects on juvenile survival and growth

Abstract: The effect of 1-year-old Monoporeia (=Pontoporeia) affinis on the survival and growth of young of the year was studied in laboratory experiments. Amphipods were kept in jars with sediment and a continuous supply of cooled water for 3 months. Adults or juveniles were added to a control density of juveniles. Juvenile mortality increased at higher total densities, and was greater when adults were present. The mean length and dry weight of juveniles decreased at higher densities, but adults did not have a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…Results from field surveys conducted by Sarvala (1986) and Lehtonen & Andersin (1998) indicate that both growth and mortality in juvenile Monoporeia affinis are dependent on the density of adults. In addition, Hill (1992) showed similar results in her laboratory study, and found evidence for food competition in adults (1+) when using baker's yeast as source. Along with our results, that growth of juveniles was densitydependent of adults, but only in the presence of added food; there exists a body of evidence that give strong support to the hypothesis that intraspecific competition for food between older age classes and juveniles acts as an important process causing abundance changes in Baltic Sea populations of M. affinis.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Results from field surveys conducted by Sarvala (1986) and Lehtonen & Andersin (1998) indicate that both growth and mortality in juvenile Monoporeia affinis are dependent on the density of adults. In addition, Hill (1992) showed similar results in her laboratory study, and found evidence for food competition in adults (1+) when using baker's yeast as source. Along with our results, that growth of juveniles was densitydependent of adults, but only in the presence of added food; there exists a body of evidence that give strong support to the hypothesis that intraspecific competition for food between older age classes and juveniles acts as an important process causing abundance changes in Baltic Sea populations of M. affinis.…”
Section: Discussionsupporting
confidence: 66%
“…However, in juveniles, a density-dependent trend for mortality was detected at the lowest food level both with and in the absence of adults, which may indicate a small contribution of directly damaging crowding effects. The data therefore cannot exclude the possibility that adults may directly harm juveniles, as suggested by Hill (1992), who found greater mortality in juveniles at high adult densities. Our data showed that juveniles under normal food regimes and high density of adults were only marginally larger than juveniles without food.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations